المعرفة العاطفية وعلاقتها بحيوية الضمير لدى طلبة جامعة الموصل. - حمد حسن هلال; أحمد وعد الله حم&#1583 (Journal of Babylon Center for Humanities Studies, 2026)
The current research aims to identify the level of emotional knowledge and the level of conscience vitality among students of the University of Mosul and the relationship between them. The basic research sample consisted of (827) male and female students who were selected by simple random method from (12) colleges at the University of Mosul for the academic year (2023-2024), with (6) morning colleges and (6) evening colleges, represented by (6) scientific colleges and (6) humanities. In order to achieve the research objectives, the researchers built a scale of emotional knowledge, which in its final form consists of (42) items with (5) alternatives, which are (applies to me to a very large extent, applies to me to a large extent, applies to me to a medium degree, applies to me to a small degree, applies to me to a very small degree). After verifying its apparent and construct validity, as well as its reliability extracted by the retest method, which reached (0.82), and the Cronbach's alpha method, which reached (0.85), the Conscientiousness Scale prepared by (Taha, 2021) was adopted. In its final form, it consists of (38) items with (5) alternatives: (applies to me very much - applies to me greatly - applies to me moderately - applies to me slightly - does not apply to me). After verifying its apparent and construct validity, as well as its reliability extracted by the retest method, which reached (0.81) and the Cronbach's alpha method, which reached (0.84), and after applying the research tools, the data were statistically processed using the Statistical Package for the Social Sciences (SPSS) program. The results showed: The research sample is characterized by high emotional knowledge, which leads them to understand many aspects of emotional life and its requirements, The research sample was characterized by high levels of conscientiousness.There is a weak, positive correlation between emotional knowledge and conscientiousness.